(untitled) (Research, Society and Development, 2024)
The use of wastewater from pig farming in agriculture, must integrate production systems that provide economic gains and environmental balance. This work aimed to evaluate the performance of the morphological components of the sorghum plant cultivar “BRS Ponta Negra” under the input of different doses of swine wastewater (ARS). The experiment was installed in the experimental area of ​​IFCE Crato – CE, in polyethylene bags with a volume of 4.9 dm3, containing 6.9 kg of soil and placed outdoors. The experiment was conducted in a randomized block design, with four treatments and four replications. The treatments consisted of four doses of ARS (D1 = 0; D2 = 0.25; D3 = 0.50 and D4 = 0.75 L pl-1) applied in three phenological stages of the crop. The plant components that obtained significance (p < 0.05) and adjusted to quadratic regression models in response to ARS doses were: leaf green mass, leaf dry mass, stem green mass, stem dry mass, plant seal and dry mass of the plant; with increments from the D1 dose to the D4 dose for these variables, by 74.57; 12.34; 191.50; 120.03; 50.06; 18.76; 255.92 and 142.69 g respectively.